Analyzing The Performance Of Cooperative Services At Padaidi Jaya To Increase Member Welfare - Saefullah, Aep; Abas, Farhat; Pardian, Ramadani (President University, 2023)
Padaidi Jaya Cooperative is a cooperative under two foundations namely Graha Ganesha Education Foundation (YPGG) and Aldian Nusantara Foundation (YAN) which consists of STIE Ganesha lecturers and Vocational Tourism teachers. The research aims to a) how the performance of Padaidi Jaya cooperative services to members, b) what economic benefits are received by members, and c) what efforts should be made to improve the welfare of members. The research method uses a descriptive qualitative approach. Data processing techniques are taken through field observations, interviews, and literature. The research was conducted for five months from January to May 2023 with 100 members of the Padaidi Jaya cooperative. The results showed that the performance of the Padaidi Jaya cooperative management in providing services to members was very good, members were satisfied with the program that had been carried out by the management. Padaidi Jaya cooperative members get many benefits of economic benefits received by children's education funds, and food vouchers every month. In order to improve the welfare of members, the Padaidi Jaya cooperative management holds programs including a) saving and borrowing money with low services, so that members can save money and borrow when there is an urgent need, of course, this is in accordance with the process of administrative terms and conditions that apply in the internal cooperative organization, b) procuring electronic goods needed by members such as laptops and gadgets, c) providing household appliances d) home installment loans (KPR). The limitations of this study are within the scope of Padaidi Jaya cooperative members consisting of two educational foundations located on Legoso Raya Street, Pisangan Village, East Ciputat District, South Tangerang City. This study contributes to the service and program solutions to improve the welfare of members.